Ikan Clariidae di Kawasan Sungai Bagandis Desa Pagatan Besar Kabupaten Tanah Laut sebagai Bahan Pengayaan SMA Berbentuk E-Booklet - Nilasari, Nilasari; Halang, Bunda; Hardiansyah, Hardiansyah (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
Pagatan Besar Village is an area characterized by wetlands such as rivers, rice fields, and swamps that support diverse aquatic life, including various fish species. Fish serve as an important source of nutrients for human survival and also possess educational potential as learning and enrichment materials. This study aims to identify the types of Clariidae fish found in the Bagandis River, Pagatan Besar Village, Tanah Laut Regency, and to assess the validity and readability of an e-booklet developed as enrichment material for the Animalia concept in senior high school biology. The research employed the Research and Development (R&D) method following the Borg and Gall model, which includes several stages: research and information collecting, planning, developing the preliminary form of the product, preliminary field testing, and main product revision. The research results identified two species of Clariidae fish, namely Clarias nieuhofi and Clarias batrachus. The validity test obtained a score of 85.35%, categorized as “very valid,” while the readability test achieved a score of 85.92%, categorized as “very good.” These findings indicate that the e-booklet developed on Clariidae fish is feasible and effective for use as enrichment material in senior high school biology learning.